Racismo estrutural e trabalho escravo contemporâneo: Uma análise sobre as relações trabalhistas em Paracatu - Macedo, Nathiele Santos (2024)
Contemporary slave labor persists in several countries, including Brazil. Paradoxically, this phenomenon is part of Brazilian social reality even with internationally recognized combat policies. Given its complexity, for an in-depth analysis of this practice in the Brazilian context, it is fundamental to consider the social markers of class, gender, and, above all, race. The legacy of slave labor during the colonial period, marked by structural racism, shaped post-abolitionist public policies, perpetuating the social and economic marginalization of the Black population. In this sense, this study aims to investigate whether structural racism influences the configuration of contemporary slave labor in Brazil, taking the city of Paracatu, Minas Gerais, as the research locus. Based on data, interviews, bibliographic research, and theoretical contributions from authors such as Lélia González, Maria Sylvia de Carvalho Franco, and Rayssa Roussenq, the study seeks to understand whether the dynamics observed in Paracatu are representative of national reality. The hypothesis is that, in addition to economic factors, racial markers play a fundamental role in leading individuals to labor exploitation in the mold of the phenomenon analyzed.